Determinants of Diarrhea Among Under-Five Children in Indonesia: A Cross-Sectional Analysis of the 2022 Indonesian Nutritional Status Survey (SSGI) - Dina Dwi Nuryanai; Wayan Aryawati; Ijlal Maajid; Christin Angelina F; Nova Muhani; Rohman Daka (Media Publikasi Cendekia Indonesia, 2026)
Diarrhea remains a major public health problem among children under five in Indonesia and contributes substantially to morbidity, malnutrition, and impaired child development. Multiple healthcare, environmental, nutritional, and behavioral factors may influence diarrhea incidence among children. This study aimed to identify the determinants of diarrhea among under-five children in Indonesia using data from the 2022 Indonesian Nutritional Status Survey (SSGI). This study used a cross-sectional design based on secondary data from the 2022 SSGI. A total of 39,125 children under five were included in the analysis. Independent variables included healthcare access, nutritional status, complementary feeding practices (MP-ASI), source of drinking water, exclusive breastfeeding, and immunization status. Data were analyzed using Chi-square tests and multivariate logistic regression with a significance level of p < 0.05. Results the prevalence of diarrhea among under-five children was 4.1%. Bivariate analysis showed significant associations between diarrhea incidence and healthcare access, nutritional status, drinking water source, and immunization status (p < 0.05). In the multivariate analysis, healthcare access (OR = 0.484; 95% CI: 0.437–0.536), nutritional status (OR = 1.110; 95% CI: 1.036–1.189), complementary feeding practices (OR = 0.924; 95% CI: 0.860–0.994), drinking water source (OR = 1.197; 95% CI: 1.022–1.403), and immunization status (OR = 1.310; 95% CI: 1.220–1.407) remained significantly associated with diarrhea incidence. Incomplete immunization was identified as the most dominant determinant of diarrhea among under-five children. Diarrhea among under-five children in Indonesia is influenced by multiple healthcare, nutritional, and environmental determinants. Strengthening immunization coverage, improving access to healthcare services and safe drinking water, and enhancing nutrition and hygiene education are essential to reduce diarrhea incidence among Indonesian children.